Efektivitas Pemberian Cairan Infus Hangat Terhadap Kejadian Menggigil Pada Pasien Sectio Caesarea Di Ruang Kamar Operasi RSUD Mukomuko - Chandra Herlani; Dilfera Hermiati; Tita Septi Handayani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Cesarean section (CS) is a surgical procedure to deliver a fetus through an incision in the abdominal wall and uterine wall. Patients undergoing cesarean section often complain of feeling cold and shivering. The purpose of this study was to determine the effectiveness of warm infusion fluids on shivering in cesarean section patients in the operating room.This study used a true experimental design, with a pretest–posttest with control group design.The results of the univariate analysis showed that at the pretest, the incidence of moderate to severe shivering (grade 2–3) was similar in both the control and intervention groups. At the posttest, there was a difference, with the intervention group showing greater improvement. Bivariate analysis results, Mann-Whitney test results on posttest data showed an Asymp. Sig. (2-tailed) value of 0.034 (< 0.05), which means there was a significant difference between the control group and the intervention group in the posttest results.The researchers recommend that healthcare workers administer warm intravenous fluids to patients experiencing shivering during cesarean section in the operating room.